Agribusiness innovation, value chain interventions, farmer input use, agricultural productivity, land access and asset ownership - Amare, Mulubrhan; Zavale, Helder; Smart, Jenny (Oxford University Press, 2024)
JEL classification: Q12, Q13, D13